2017
DOI: 10.3389/fpls.2017.01004
|View full text |Cite
|
Sign up to set email alerts
|

ANGUSTIFOLIA, a Plant Homolog of CtBP/BARS Localizes to Stress Granules and Regulates Their Formation

Abstract: The ANGUSTIFOLIA (AN) gene in Arabidopsis is important for a plethora of morphological phenotypes. Recently, AN was also reported to be involved in responses to biotic and abiotic stresses. It encodes a homolog of the animal C-terminal binding proteins (CtBPs). In contrast to animal CtBPs, AN does not appear to function as a transcriptional co-repressor and instead functions outside nucleus where it might be involved in Golgi-associated membrane trafficking. In this study, we report a novel and unexplored role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 88 publications
2
41
0
Order By: Relevance
“…AN encodes a plant homolog of C-terminal-binding protein/brefeldin A-ADP ribosylated substrate (CtBP/BARS; Folkers et al, 2002;Kim et al, 2002). AN is involved in determining leaf and cell shapes, root formation, microtubule organization, and abiotic stress responses in Arabidopsis (Tsuge et al, 1996;Folkers et al, 2002;Kim et al, 2002;Bai et al, 2013;Gachomo et al, 2013;Bhasin and Hülskamp, 2017). Our findings reveal the relationship between AN and the actin cytoskeleton in centripetal nuclear positioning in Arabidopsis leaves.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…AN encodes a plant homolog of C-terminal-binding protein/brefeldin A-ADP ribosylated substrate (CtBP/BARS; Folkers et al, 2002;Kim et al, 2002). AN is involved in determining leaf and cell shapes, root formation, microtubule organization, and abiotic stress responses in Arabidopsis (Tsuge et al, 1996;Folkers et al, 2002;Kim et al, 2002;Bai et al, 2013;Gachomo et al, 2013;Bhasin and Hülskamp, 2017). Our findings reveal the relationship between AN and the actin cytoskeleton in centripetal nuclear positioning in Arabidopsis leaves.…”
mentioning
confidence: 70%
“…We identified DYRKP-2B as an AN-interacting protein (Fig. 8); its homolog DYRKP-1 also interacts physically with AN (Bhasin and Hülskamp, 2017). DYRKP-1 and DYRKP-2B are members of a plant-specific subgroup in the DYRK family (Kajikawa et al, 2015), which is widely conserved in animals, plants, fungi, and protists, and is involved in developmental processes, cell homeostasis, and cellular stresses (Aranda et al, 2011).…”
Section: An Associates With the Protein Kinases Dyrkpsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, ANGUSTIFOLIA, which localizes to stress granules and regulates stress granules formation, was shown to interact also with the Glycine-rich RNA-binding protein 7. The latter protein might therefore be casual to the common localization of ANGUSTIFOLIA and ArathEULS3 in the stress granules [8]. All this evidence suggests that, even if ArathEULS3 does not bind directly to nucleic acids, it could be a part of a larger protein complex together with the Glycine-rich RNA-binding protein, which regulates transcription processes.…”
Section: Discussionmentioning
confidence: 99%
“…So far, nothing has been published about the biological role of SIK1-3. A recent study also showed interaction between SIK1 (AIK1) and AN in a yeast-twohybrid assay (Bhasin & Hülskamp, 2017). SIK1 to 3 are part of the Dual-specificity tyrosine-regulated kinases (DYRK) protein kinase family of which only one member has been studied in plants (Shiu et al, 2004).…”
Section: Sok Proteins Share Interaction Partnersmentioning
confidence: 98%